Stakeholder’s Perspective on the Challenges Faced during the Implementation of the Integrated Curriculum at Medical Colleges of Khyber Pakhtunkhwa - Shahzadi, Shimee; Jamil, Brekhna; Adeeb, Humera; Shah, Muhammad; Khan, Shehzad Akbar (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To explore and identify the challenges stakeholders face in implementing and sustaining the integrated curriculum in undergraduate medical colleges of Khyber Pakhtunkhwa METHODOLOGY The study design was qualitative exploratory. A total of 15 participants (student, faculty member, and educationist from each institute, two public sector and three private sector medical colleges in Peshawar. The participants meeting the inclusion criteria were enrolled through a purposive sampling technique. An interview guide was developed based on the literature review, and experts’ validation was done and used to conduct semi-structured interviews with nine participants. A Focused group discussion (FGD) comprised six participants to complement the data from individual interviews. Audio recordings of interviews and FGD were transcribed verbatim manually. The ten transcripts were fragmented and searched for primary codes. A total of 166 codes in vivo codes were generated. The second cycle of 44 descriptive codes was defined. The secondary codes were merged into 17 subthemes and six themes. RESULTS A total of six themes were derived from the data. The themes were that planning curriculum integration is like planning an uphill drive, dream versus ground reality, moving up and down the ladder, teamwork is the heart of the paradigm shift, the challenges, and the road to success. Participants views on the difficulty of implementing an integrated curriculum varied widely, and these differences were attributable to the participants’ unique perspectives and contextual factors of the institutes. CONCLUSION Implementing an integrated curriculum is not a journey on the road; it faces many challenges. Teamwork is the hallmark of successful implementation.